2019
DOI: 10.21451/1984-3143-ar2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Association between gestation length and lactation performance, lactation curve, calf birth weight and dystocia in Holstein dairy cows in Iran

Abstract: In this study, 252,798 lactations on 108,077 cows in 433 herds were used to determine the association between gestation length (GL) and lactation performance, lactation curve, calf birth weight and dystocia in Holstein dairy cows in Iran. The GL averaged 278.1 ± 5.41 d, was categorized as short (SGL; at 1 SD below the population mean), average (AGL; the population mean ± 1 SD), or long (LGL; at least 1 SD above the population mean). Factors including parity, calf gender and calving season were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…The differences reported in other studies may be explained by different breeds and farming conditions. Different values of peak yield and day of peak was described by many authors [1,2,5,7,14]. 37 % of the total milk yield) was produced in the period between 306 and 547 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences reported in other studies may be explained by different breeds and farming conditions. Different values of peak yield and day of peak was described by many authors [1,2,5,7,14]. 37 % of the total milk yield) was produced in the period between 306 and 547 days.…”
Section: Methodsmentioning
confidence: 99%
“…Czech dairy Simmental cattle belongs to the family of dual-purpose breeds of the phylogenetic group of "Simmental type breed" as well as other breeds derived from Simmental cattle such as Fleckvieh, Montbé liarde and Pezzata Rossa. The description of lactation curve is still current in livestock research and was analysed by many authors [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Atashi and Asaadi [77], using 252,798 lactations on 108,077 Holstein dairy cows in Iran showed that multiparous cows with longer gestations performed better in lactation than primiparous cows. This study also showed that multiparous cows with short gestation length had a lower yield at the beginning of lactation and higher raising and declining slopes of the lactation curve compared with cows presenting longer or average length of pregnancy.…”
Section: Pregnancy and Lactation Lengthmentioning
confidence: 99%
“…It is also known that there is a higher frequency of dystocia in male calves' birth [60,74,79]. Dystocia significantly reduces the whole lactation milk yield [40,50,54,69,[75][76][77], besides increasing veterinary treatment costs [76], and reducing cow fertility. After dystocia there is a higher incidence of metritis [77], ketosis [80,81], both associated with a decrease in milk production.…”
Section: Calving Difficultymentioning
confidence: 99%
See 1 more Smart Citation